[updated from 2017] Aflasafe product for Nigeria - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Aflasafe, a biocontrol product developed for use in maize and groundnut in Nigeria, was approved by the regulatory authority Nigeria National Food and Drug Administration and Control in 2014. The product is manufactured and commercialized by the company HarvestField Industries